Rapid, specific, and sensitive detection of the ureR_1 gene in Klebsiella pneumoniae by loop-mediated isothermal amplification method - Li,Chao (2019)
Klebsiella pneumoniae is one of the main pathogenic bacteria that causes nosocomial infections, such as pneumonia, urinary tract infection, and sepsis. Therefore, the rapid and accurate detection of K. pneumoniae is important for the timely treatment of infectious patients. This study aimed to establish a loop-mediated isothermal amplification (LAMP) method for the rapid and sensitive detection of K. pneumoniae-specific gene ureR_1 (Gene ID: 11847803). The ureR_1 gene was obtained through local and online BLAST, and the specific primers were designed for its detection. Positive reactions were observed on all 140 K. pneumoniae clinical isolates while all the 82 non-K. pneumoniae clinical isolates were negative. Plasmids with the specific gene and the mouse blood with K. pneumoniae were used for sensitivity analysis. The detection limit of the LAMP was 1 bacterium/reaction. The results showed that the LAMP targeted to ureR_1 is a fast, specific, sensitive, inexpensive, and suitable method for the detection of K. pneumoniae.